Gold-based metal-organic framework containing copper or nickel for simultaneous electrochemical detection of dopamine and uric acid - Zhou, Feng (2023)
The rapid and efficient detection of small biomolecules in human body fluids is a critical step in developing effective electrode materials. Metal-organic frameworks (MOFs) have gained significant attention from researchers due to their unique properties, such as remarkable surface area and tunable pore size. An Au@Cu-metal-organic frameworks (Au@Cu-MOFs) composite material has been successfully synthesized via one-pot solvothermal method. The composite material was modified onto a screen-printed carbon electrode (SPCE) to serve as an electrocatalyst for the oxidation of dopamine (DA) and uric acid (UA). The inclusion of gold nanoparticles (Au NPs) on the octahedral crystal shape of Cu- MOFs has dramatically improved the catalytic performance of the developed sensor. The electrochemical performance of the proposed sensor based on Au@Cu-MOFs toward simultaneous detection of DA and UA shows an extended linear range from 1 μM to 1000 μM, with good sensitivity and remarkably lower detection limits (LOD) of 2.12 μA μM-1 cm-2 and 0.06 μM for DA, as well as 1.76 μA μM-1 cm-2 and 0.08 μM for UA. Another composite material of MOF by using different metal center (Au@Ni- MOF) was developed for comparison. The composite material of Au@Ni-MOF was prepared via two-step approach. Firstly, Ni-MOF was synthesized using an in-situ growth strategy, which involved the growth of [Ni3(BTC)2] n (H3BTC = trimeric acid) with coordinatively unsaturated Ni(II) sites. Then, the assynthesized Ni-MOF powder was mixed with the Au NPs solution to produce the Au@Ni-MOF hybrid material. This sensor demonstrated LODs of approximately 0.027 and 0.028 μM for the simultaneous determination of DA and UA (S/N = 3) over a wide linear range of 0.5 μM to 1 mM, with an excellent sensitivity of 1.43 μA μM-1 cm-2 and 1.35 μA μM-1 cm-2, respectively. The application was further investigated in human serum and urine for the simultaneous determination of DA and UA, which also showed exceptionally high recovery in the 93.8% to 105.0% range with a lower RSD of less than 3%. In conclusion, there is a great need for rapid, efficient, and highly sensitive detection of small biomolecules by improving novel MOF-based electrode materials in medical research. Therefore, we evaluated the analytical performance of Au@M-MOF electrodes (M = Cu and Ni) and successfully applied them to determine simultaneous DA and UA in human urine and serum samples.